Change in Hematological disturbances in Malaria in Eastern India: an observational study - Mukherjee, Joydeep; Chakrabarty, Pradeep; Sinharoy, Uma; Brojobasi, Bhaskar (Bangladesh Journal of Medical Science, 2016)
Objectives: We wanted to find out the change and pattern of hematological disturbances in patients suffering from malaria and whether the hematological disturbances had any correlation with morbidity in them. Materials and methods: In a retrospective, observational study, first 100 admitted malaria patients in a tertiary medical institute in Kolkata, was taken from August 2009 to July 2011 and their demographic, clinical and laboratorial records were noted and analysed. Results: Seventy-one patients (71%) had anemia, ninety patients (90%) had thrombocytopenia, twenty-six patients (26%) had leucopenia and two patients (2%) had leukocytosis. Vivax malaria patients had lower platelet count than their falciparum counterparts, whereas falciparum malaria patients had lower hemoglobin, packed cell volume and higher total leukocyte count; all these hematological disturbances were found to be correlated with higher morbidity in patients suffering from malaria. Conclusion: In patients suffering from malaria, there was high incidence of hematological disturbances which was changing pattern and also correlated with morbidity. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.403-408